Effect of complete rumen modifier (CRM) and Calliandra calothyrus on productivity and enteric methane productions of PE dairy goat - Ni Made Suci Sukmawati; I.G. Permana; A. Thalib; S. Kompiang (Indonesian Center for Animal Research and Development (ICARD), 2011)
Methanogenesis in the rumen is thought to represent 2-12% loss of energy intake. The energy loss as methane can decrease animal productivity and feed efficiency. In addition, methane is potentially involves in global warming that affects the atmosphere adversely. A research to improve PE dairy goat productivity and reduce enteric methane emission by supplementation of calliandra and complete rumen modifier (CRM) was conducted for 6 months. In this experiment 20 PE dairy goats were divided into five blocks according to body weight. The experimental design used was a randomized block design that consisted of four treatments, A). Elephant grass 50% + concentrate 50% (control), B). Elephant grass 40% + concentrate 40% + calliandra 20%, C). Elephant grass 50% + concentrate 48% + CRM 2% and D). Elephant grass 40% + concentrate 38% + calliandra 20% + CRM 2%. Data were analyzed statistically using ANOVA and Duncan test. The result showed that calliandra and CRM did not affect nutrient consumption, except that protein consumption increased (P < 0.05) in calliandra treatments (B and D). Nutrient digestibility increased in CRM (C) treatment, while other treatments did not differ from control. CRM also increased total bacteria (36.84%), milk production (67.21%), milk fat (25.0%), and reduced enteric methane production (65.71%). The improvement of milk production in CRM treatment (C) was followed by better feed efficiency than other treatments. In conclusion, CRM was more effective than calliandra in improving milk production of PE dairy goats and reduced enteric methane emission, but its effectivity was reduced in combination with calliandra. Key Words: Dairy Goat, Calliandra, Rumen Modifier, Methane, Productivity